Affordable housing in US shrinking cities : from neighborhoods of despair to neighborhoods of opportunity? /: from neighborhoods of despair to neighborhoods of opportunity?. (2016) - Silverman, Robert Mark, 1967-; Patterson, Kelly L; (Of State University of New York at Buffalo), Yin, Li; Ranahan, Molly; Wu, Laiyun
No abstract available